2019
DOI: 10.1002/fam.2694
|View full text |Cite
|
Sign up to set email alerts
|

Effects of static pressure, pressurization, and depressurization on n‐heptane pool fires in an airplane cargo compartment

Abstract: Summary The cargo compartment of an airplane in flight is a complex environment with dynamic pressure (pressurization and depressurization), nonconservative oxygen, and unidirectional ventilation. In this study, n‐heptane pool fires were performed under static pressure, pressurization, and depressurization in a full‐scale airplane cargo compartment. The static pressure included 30 and 90 kPa, the pressurization was from 30 to 90 kPa at rates of 6, 12, 19, and 25 kPa/min, while the depressurization was from 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The random error was mainly caused by radiation loss from the thermocouple joint. According to a previous study, 19 with thermocouples, 2 mm in diameter, radiation inaccuracy for corrected flame temperature based on energy balance shows fuel temperature measurement uncertainty of less than 5% in the temperature range 300 K to 1000 K. For uncertainty components that are caused by fuel temperature, total temperature measurement error is much lower than the flame temperature as a result of the low temperature of the fuel itself. The experiments were repeated for each group as a means of enhancing reliability.…”
Section: Experimental Designmentioning
confidence: 94%
See 1 more Smart Citation
“…The random error was mainly caused by radiation loss from the thermocouple joint. According to a previous study, 19 with thermocouples, 2 mm in diameter, radiation inaccuracy for corrected flame temperature based on energy balance shows fuel temperature measurement uncertainty of less than 5% in the temperature range 300 K to 1000 K. For uncertainty components that are caused by fuel temperature, total temperature measurement error is much lower than the flame temperature as a result of the low temperature of the fuel itself. The experiments were repeated for each group as a means of enhancing reliability.…”
Section: Experimental Designmentioning
confidence: 94%
“…A pressure chamber is able to simulate different pressure environments by controlling airflow and the USTC has established a small simulation chamber in Hefei 15–17 . Tsinghua University has established a plateau simulation chamber, similar to the cargo hold of an aircraft, in Kangding 18–21 . Experimental studies have shown that fuel combustion characteristics change at a different rate to pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Achievements about the fire burning behaviors under low air pressure are mostly obtained based on pool fire test. Abundant evidences have shown that fire behaviors are inherently different in a low‐pressure environment: reduction in burning rate and heat release rate, elongated flame shape 10‐21 . Research works about combustion characteristic of pool fire has made considerable progress.…”
Section: Introductionmentioning
confidence: 99%
“…Although flammable materials are limited strictly on commercial aircraft, potential fire risk still exists . In recent days, many researchers have investigated cargo compartment fire, including the ceiling temperature, smoke concentration, mass burning rate and fire flume characteristics under dynamic pressure, and ceiling temperature with different ceiling heights, with different inclined ceiling angles . FAA carried out four different minimum performance standard (MPS) fire tests to determine the required concentration levels that a Halon replacement need to meet to suppress cargo compartment fire…”
Section: Introductionmentioning
confidence: 99%